Considerations for the Development of an Undergraduate Curriculum in Geriatric Medicine - Singler, Katrin; Sieber, Cornel; Biber, R.; Roller, R. E. (Gerontology, 2013)
Background: Although the number of older patients is increasing in almost all medical specialties, the interest of medical students in geriatrics as a career is still low. Because quality of medical education and educators strongly influences student career decisions, it is important to develop curricula that motivate students to become self-directed, lifelong learners in the field of geriatric medicine. Objectives: We evaluated training aspects in terms of time, core content of teaching goals, and quality of undergraduate geriatric education in medical schools in Austria and Germany. Methods: A standardized paper questionnaire was sent to all 36 German and 4 Austrian medical faculties to evaluate quantitative aspects, content, and quality of pregraduate medical education in geriatrics. Results were compared to the recommendations of the Geriatric Medicine Section of the European Union of Medical Specialists (UEMS). Results: A total of 33/36 (92 of the German medical faculties) and 4/4 (100 of the Austrian medical faculties) responded to the questionnaire. In most of the faculties, geriatric medicine was taught as an independent discipline in the core curriculum, with learning objectives absent in almost one third of the faculties. A medical student's first contact with geriatric medicine occurred on average during the second clinical year (median 8th semester). Although the content of geriatric curricula strongly varied among the faculties, core knowledge as recommended by the UEMS was integrated into most of the curricula. Teaching strategies regarding the development of attitudes and skills also recommended by the UEMS were identified in the curriculum of only some faculties. Conclusions: Geriatrics seems to be an established subject in most German and Austrian faculties. However, the current data clearly indicate highly variable quality in geriatric pregraduate training at German and Austrian universities. Because curricula should prepare young people using competence-based training and assessment methods, room for improvement remains not only in terms of structure, but also regarding quality of training to develop self-directed life-long learners. Copyright (C) 2013 S. Karger AG, Basel
Keywords: Medical education; Geriatrics; Curriculum development; Learning objectives; Educational strategies